Perbandingan Verifikasi Peserta Pemilu Tahun 2019 dan 2024 - Sultan, Wabil Fadli; Tamma, Sukri; Yunus, Ariana (Palita: Journal of Social Religion Research, 2022)
This paper focuses on the Comparison of Verification of Election Contestants in 2019 and 2024. In addition, this paper describes the problems that arise during the verification process. In this study, the author uses a qualitative method. The data used in the study consisted of primary and secondary data. The data collection method in this study used the Literature Study Technique. The author uses scientific papers such as journals, theses, and state documents in collecting data. The data collected by the author is then processed according to the needs of the analysis carried out. The results of the research show that the basic difference regarding the verification process for election participants in 2019 and 2024 is that there is no factual verification for Parliamentary parties participating in the 2024 election. The most basic problem of any verification carried out is the membership of political parties that still have members' names. The impact of such profiteering is the rights of the community that can cause harm, especially for job seekers because of the provisions of not being involved as administrators and/or members of political parties. It is necessary to carry out factual verification of management, office domicile and verification of membership without distinguishing between small and large parties in a proportional and fair manner. With integrity in the verification of political parties, it will produce public officials from credible and qualified political parties.